Influence of light conditions on adult mortality and egg-laying of Triatoma brasiliensis neiva, 1911 (Hemiptera: Reduviidae: Triatominae) - Carlos Brisola Marcondes; João Agnaldo Nascimento (Revista da Sociedade Brasileira de Medicina Tropical, 1992)
We compared, for Triatoma brasiliensis, the egg-laying process and the mortality of adults under conditions of almost permanent darkness and with normal laboratory luminosity. Mortality did not differ between groups. The egg-laying per vial and per female was significantly greater in the group of normal luminosity. We consider that it is not recommendable to keep the adults of this species under complete darkness. Other biological aspects should be analysed in relation to luminosity.